Allergen bronchoprovocation test: an important research tool supporting precision medicine - Boulet, Louis-Philippe; Côté, Andréanne; Abd-Elaziz, Khalid; Gauvreau, Gail; Diamant, Zuzana (Current opinion in pulmonary medicine, 2021)
PURPOSE OF REVIEW: Allergen bronchoprovocation test (ABT) has been used to study asthma pathophysiology and as a disease-modelling tool to assess the properties and efficacy of new asthma drugs. In view of the complexity and heterogeneity of asthma, which has driven the definition of several phenotypes and endotypes, we aim to discuss the role of ABT in the era of precision medicine and provide guidance for clinicians how to interpret and use available data to understand the implications for the benefits of asthma treatment. RECENT FINDINGS: In this review, we summarize background knowledge and applications of ABT and provide an update with recent publications on this topic. In the past years, several studies have been published on ABT in combination with non-invasive and invasive airway samplings and innovative detection techniques allowing to study several inflammatory mechanisms linked to Th2-pathway and allergen-induced pathophysiology throughout the airways. SUMMARY: ABT is a valuable research tool, which has strongly contributed to precision medicine by helping to define allergen-triggered key inflammatory pathways and airway pathophysiology, and thus helped to shape our understanding of allergen-driven asthma phenotypes and endotypes. In addition, ABT has been instrumental to assess the interactions and effects of new-targeted asthma treatments along these pathways.
Keywords: respirační funkční testy; individualizovaná medicína; Bronchial Provocation Tests; Respiratory Function Tests; fenotyp; Asthma; Humans; Phenotype; Precision Medicine; lidé; bronchiální astma; Allergens; alergeny; bronchoprovokační testy